(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present study was directed to figure out the difference in level of strength of major groupof muscles concerned with Judokas of light weight category. Switching to next weight category hasalways been considered a challenging task for any combative sports. To know whether switching to -66kg from -60kg weight category requires significant improvements in selected strength parameters. Atotal of 34 Judokas were recruited to achieve the objectives of this study. 19 Judokas from -60kg weightcategory, and 15 Judokas of -66kg weight category took part in this study voluntarily. For statisticalanalysis Independent sample t-test was applied, level of significance was set at 0.05 during wholestatistical analysis. Their performance were tested on grip strength, bench press, back strength, legstrength. Results of the study suggests that except back strength the strength levels of Judokas of twoselected weight categories varies significantly from each other.